A Convenient Verisimilitude or Oppressive Internalization? Characterizing the Ethical Arguments surrounding Hierarchical Structures in Knowledge Organization Systems - Tennis, Joseph T. (Knowledge Organization, 2017)
This paper considers the ethical concerns that surface around hierarchy as structure in knowledge organization systems. In order to do this, I consider the relationship between semantics and structure and argue for a separation of the two in design and critique of knowledge organization systems. The paper closes with an argument that agency and intention, as ethical concerns in knowledge organization, lead us to argue for a neutral stance on hierarchy.